(untitled) (Research, Society and Development, 2021)
Failure Modes and Effects Analysis (FMEA) is a risk management tool that offers an elaborate approach to assess, control and update the progress of projects, where any risk that affects quality, reliability or safety must be assessed and described in FMEA for failure prevention. Engineering projects consist of work carried out in colleges by teachers and students to develop new skills and competences. In addition, these projects provide practical application of knowledge seen in theory, preparing students for the job market, encouraging innovation and integration with social and environmental issues. This work presents a case study on the use of FMEA in the steering wheel coupling and uncoupling system in the steering bar of an engineering project that aims to automate a golf cart. The results found consist of the identification of failure modes and the calculation of the respective RPN, as well as the elaboration of an action plan to reduce or eliminate it. This work also found the importance of graduating students to know and use the tool, given that its understanding and application can also develop competencies and skills such as critical analysis, sequenced and ordered thinking, in addition to acting in the team with the objective of eliminating waste and optimizing projects, processes, systems and services.